2018
DOI: 10.1111/jocn.14605
|View full text |Cite
|
Sign up to set email alerts
|

Clinical nurses’ experiences and perceptions after the implementation of an interprofessional team intervention: A qualitative study

Abstract: Effective teamwork and communication between multiple healthcare professionals including nurses are the cornerstones to improve care delivery, nursing outcomes and quality of patient care in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…A key purpose of clinician experience data is the provision of information from clinicians about factors that encouraged or enabled them to adopt, adhere or adapt to new practices, technologies and circumstances. Most studies identified in the peer-reviewed and grey literature were focused on clinician experiences of change related to a specific event or project and clinicians were viewed as critical to ensuring that proposed health service or system changes was taken up in practice so that benefits could be realised [19,23,25,75,76].…”
Section: Discussionmentioning
confidence: 99%
“…A key purpose of clinician experience data is the provision of information from clinicians about factors that encouraged or enabled them to adopt, adhere or adapt to new practices, technologies and circumstances. Most studies identified in the peer-reviewed and grey literature were focused on clinician experiences of change related to a specific event or project and clinicians were viewed as critical to ensuring that proposed health service or system changes was taken up in practice so that benefits could be realised [19,23,25,75,76].…”
Section: Discussionmentioning
confidence: 99%
“…A key purpose of clinician experience data is the provision of information from clinicians about factors that encouraged or enabled them to adopt, adhere or adapt to new practices, technologies and circumstances. Most studies identi ed in the peer-reviewed and grey literature were focused on clinician experiences of change related to a speci c event or project and clinicians were viewed as critical to ensuring that proposed health service or system changes was taken up in practice so that bene ts could be realised (19,23,25,76,77).…”
Section: Discussionmentioning
confidence: 99%
“…A key purpose of clinician experience data is the provision of information from clinicians about factors that encouraged or enabled them to adopt, adhere or adapt to new practices, technologies and circumstances. Most studies identified in the peer-reviewed and grey literature were focused on clinician experiences of change related to a specific event or project and clinicians were viewed as critical to ensuring that proposed health service or system changes was taken up in practice so that benefits could be realised (18,22,24,75,76).…”
Section: Discussionmentioning
confidence: 99%